2020
DOI: 10.3389/fpsyg.2020.587911
|View full text |Cite
|
Sign up to set email alerts
|

Ageism and Behavior Change During a Health Pandemic: A Preregistered Study

Abstract: The COVID-19 pandemic has led to a suspected surge of ageism in America and has imposed critical health and safety behavior modifications for people of all ages (Ayalon et al., 2020; Lichtenstein, 2020). Given that older adults are a high-risk group, maintaining their safety has been paramount in implementing preventive measures (i.e., more handwashing, social distancing); however, making such behavior modifications might be contingent on how one views older adults (i.e., ageist stereotypes). Therefore, the go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
2
25
0
2
Order By: Relevance
“…In this sense, some society support (mainly long-term care and adult children) has been directed towards protect older adults with overaccommodative polices and/or behaviours (such as avoiding contact with or sequestering older adults) that may undermine older adults' autonomy, their right to make their own health-based decisions and even their social and emotional wellbeing [21,47]. Vale et al [48] showed that both hostile and benevolent ageism predict divergent responses to the pandemic; while hostile ageism is associated with less pandemic-related health and safety precautions, benevolent ageism is related to increased behaviour changes, but only as a result of increased pandemic-related fear. These findings are fundamental for developing programmes or policies representing older people in the context of the pandemic, as well as in deciding which messages to use, because they may have indirect consequences on how older people are viewed and thus treated [42,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some society support (mainly long-term care and adult children) has been directed towards protect older adults with overaccommodative polices and/or behaviours (such as avoiding contact with or sequestering older adults) that may undermine older adults' autonomy, their right to make their own health-based decisions and even their social and emotional wellbeing [21,47]. Vale et al [48] showed that both hostile and benevolent ageism predict divergent responses to the pandemic; while hostile ageism is associated with less pandemic-related health and safety precautions, benevolent ageism is related to increased behaviour changes, but only as a result of increased pandemic-related fear. These findings are fundamental for developing programmes or policies representing older people in the context of the pandemic, as well as in deciding which messages to use, because they may have indirect consequences on how older people are viewed and thus treated [42,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Protecting older adults has been emphasized in the effort to increase compliance with public health advice. Implementing social restrictions on all people over a certain age however is problematically ageist, classifying older adults as a homogenous risk, and undermining their autonomy [15]. Restrictions seem to commonly have negative effects on physical and psychological well-being of older patients.…”
Section: Discussionmentioning
confidence: 99%
“…İleri yaştaki bireylerin salgın açısından daha yüksek risk altında olduğu bilgisi sonucunda sokağa çıkma kısıtlamalarını ve önleyici tedbirleri bu doğrultuda belirlemek, onları korumak açısından akla yatkın görülebilir. Ancak, diğer yandan bu uygulama yaşçılığın tetikleyicisi de olabilmektedir (Ayalon et al, 2020;Lichtenstein, 2020;Vale, Stanley, Houston, Villalba, & Turner, 2020).…”
Section: Tartişma Ve Sonuçunclassified